Giant Cell Tumor of the Pes Anserine Bursa (Extra-Articular Pigmented Villonodular Bursitis): A Case Report and Review of the Literature - Haitao Zhao; Aditya V. Maheshwari; Dhruv Kumar; Martin M. Malawer (Case Reports in Medicine)
Pigmented villonodular synovitis (PVNS) is a rare, benign, proliferating disease affecting the synovium of joints, bursae, and tendon sheaths. Involvement of bursa (PVNB, pigmented villonodular bursitis) is the least common, and only few cases of exclusively extra-articular PVNB of the pes anserinus bursa have been reported so far. We report a case of extra-articular pes anserine PVNB along with a review of the literature. The lesion presented as a painful soft tissue mass in the medial part of the proximal leg. A magnetic resonance imaging showed areas of low to intermediate signals in all sequences and the lesion enhanced heterogeneously with contrast. Diagnosis was confirmed by an incisional biopsy, and an intralesional resection was performed. The postoperative course was uneventful, and the patient is free of disease with no functional deficit at 2 years followup. As with other rare lesions, clinical and radiographic findings in addition to histological examination are essential for correct diagnosis.